LINGUOCULTURAL APPROACH TO THE STUDY OF ALLUSION IN ENGLISH (Scientific journal of the Fergana State University, 2024)
In this article, we have set the goal of studying the essence of the term allusion, the established approaches to it. In the study of the essence and forms of illusionary words, such methods as system analysis, comparison, generalization were used. Economic, cultural and scientific ties of countries and their peoples are becoming more relevant as the study of intercultural communication, the relationship of language and culture, the study of linguistic identity. The analysis of the literature on the topic shows the classification of allusions within the framework of the linguacultural approach according to their function in speech. A deeper study of linguacultural specific linguistic units and stylistic techniques help to better understand the process of interaction between language and culture.